PENGARUH MEDIA PERENDAMAN AIR KERAN, AIR GARAM, DAN AIR LIMBAH DETERJEN TERHADAP PERTUMBUHAN AKAR BAWANG MERAH (ALLIUM CEPA L.) - Tri Wahyuni; Krisdayanti Febyola Angelina Ambarita; Intan Cahya Lestari; Annisa Putri Ginting; Dita Salsabila; Larasati Arum Utami (STKIP Subang, 2026)
This study aimed to analyze mitotic cell division activity in onion (Allium cepa L.) root tips soaked in salt water, detergent wastewater, and plain water. The research employed an experimental method with a descriptive approach. Onion bulbs were soaked for 48 hours, and the root tips were prepared using the squash method with acetocarmine or aceto-orcein staining before being observed under a light microscope. Observations focused on the occurrence of mitotic phases and root growth in each treatment. The results showed that the soaking media affected onion root growth differently. The plain water treatment produced approximately two short roots, allowing microscopic preparation, although mitotic phases could not be clearly identified due to suboptimal slide quality. The salt water treatment produced no root growth, likely due to plasmolysis caused by high osmotic pressure. Meanwhile, the detergent wastewater treatment caused the most severe tissue damage, indicated by discoloration and softening of tissues due to membrane disruption by surfactants. Consequently, microscopic observations could not be conducted in both treatments. It can be concluded that the quality of the soaking medium influences root growth and mitotic activity in Allium cepa L.